Bakti Sosial Operasi Katarak dalam Meningkatkan Fungsi Penglihatan dan Produktivitas Masyarakat Kurang Mampu di Tebing Tinggi - Sucipto Sucipto; Endy Juli Anto; Ronald T. H. Tambunan; Frengky S. Manullang; Widjaya Taufik Tiji; Tengku M. Fauzi; Jadeny Sinatra; Juli Jamnasi; Jekson Martiar Siahaan (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Cataracts are the leading cause of blindness worldwide and a major public health challenge, particularly among underserved populations in Indonesia. This community service activity aimed to restore vision and improve quality of life for underprivileged cataract patients through free cataract surgery provided by Lions Club Medan Angkasa and Lions Club Tebing Tinggi Royal in collaboration with Tebing Tinggi Police Department and Bhayangkara Hospital. The surgical camp was conducted on Sunday, April 27, 2025, at RS Bhayangkara Tebing Tinggi, in commemoration of the 79th Bhayangkara Anniversary. The activity included preoperative screening, phacoemulsification cataract surgery, pterygium excision, and postoperative care. A total of 79 patients participated: 73 cataract cases and 6 pterygium cases. Experienced ophthalmologists successfully performed all surgeries using modern surgical techniques. Post-operative evaluation showed significant visual improvement in 98% of patients. This initiative demonstrates the effectiveness of multi-sector collaboration in addressing preventable blindness and highlights the crucial role of community-based organizations in supporting healthcare access for marginalized populations.